Pengaruh Pendapatan Asli Daerah terhadap Pertumbuhan Ekonomi dengan Belanja Modal dan Investasi Swasta sebagai Pemoderasi - Saraswati, Ida Ayu; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 24 No 1 (2018), 2018)
Economic Growth is one of the indicators to measure the success of economic development in a country. It is hoped that with the revenues from the Local Revenue (PAD) can increase regional economic growth, the increase in PAD can increase investment of local government capital expenditures, local governments need to pay special attention in the field of private investment. This research is to know the influence of local income to economic growth with capital expenditure and private investment as moderator variable. Conducted in 8 districts and 1 municipality in Bali Province in 2012-2016. Analysis technique used in this research is by using technique of Moderated Regression Analysis (MRA) by using Statistical Product and Service Solution (SPSS) program. The results of this study show that PAD has a positive effect on economic growth. Capital Expenditure weakens the influence of PAD on Economic Growth, while Private Investment strengthens the influence of PAD on Economic Growth. Keywords: local revenue, economic growth, capital expenditure, private investment.